The Role of Brand Awareness as A Mediator in the Relationship Between Entertainment and eWOM on Brand Loyalty: An Analysis of Social Media Marketing Content. - Prasetyo, Anton; Praswati, Aflit Nuryulia (Yayasan Sinergi Kawula Muda, 2025)
This study examines the influence of social media marketing activities, specifically entertainment and eWOM (electronic word-of-mouth), on brand loyalty, with brand awareness as a mediating factor. The main objective of this study is to explore how entertainment and eWOM influence brand loyalty through brand awareness in the context of fashion product marketing on TikTok social media. This study used a quantitative method with purposive sampling, involving 120 respondents who were surveyed through questionnaires. Results show that entertainment and eWOM significantly increase brand awareness, which in turn has a positive impact on brand loyalty. In addition, brand awareness fully mediates the relationship between entertainment and eWOM regarding brand loyalty. Entertainment on TikTok can create an emotional attachment with consumers, while eWOM serves as organic marketing that influences consumer decisions. Therefore, to increase brand loyalty, brands should create entertaining content and encourage consumers to share their positive experiences through eWOM. In conclusion, brand awareness plays an important role in building brand loyalty, and engaging content marketing and strong social interaction can increase brand awareness and consumer loyalty on social media platforms such as TikTok.